2014
DOI: 10.1007/s12272-013-0326-9
|View full text |Cite
|
Sign up to set email alerts
|

(E)-2,4-Bis(p-hydroxyphenyl)-2-butenal enhanced TRAIL-induced apoptosis in ovarian cancer cells through downregulation of NF-κB/STAT3 pathway

Abstract: Ovarian cancer is a cancerous growth arising from the ovary and with poor prognosis that usually have resistant to all currently available treatments. Whether (E)-2,4-bis(p-hydroxyphenyl)-2-butenal (butenal) synthesized by Maillard reaction from fructose-tyrosine, has potential therapeutic activity against human ovarian cancer was investigated using two ovarian cancer cell lines (PA-1, SK-OV-3). We found that butenal could inhibit NF-κB/STAT3 activity, thereby inducing apoptotic cell death of ovarian cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…16 CCDO-Me, a synthetic triterpenoid, inhibits expression of STAT3 phosphorylation in multi-drug resistant ovarian cancer cells. 17 Similarly, in our previous study, we found that (E)-2,4-bis (p-hydroxyphenyl)-2-butenal enhanced TRAIL-induced apoptosis in ovarian cancer cells via down regulation of STAT3 pathway, 18 bee venom toxin and melittin suppressed ovarian cancer cell growth through induction of death receptors and inhibition of STAT3 pathway. 19 Moreover, it was demonstrated that blocking STAT3 activation with shRNA or siRNA could suppress ovarian cancer cell growth.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…16 CCDO-Me, a synthetic triterpenoid, inhibits expression of STAT3 phosphorylation in multi-drug resistant ovarian cancer cells. 17 Similarly, in our previous study, we found that (E)-2,4-bis (p-hydroxyphenyl)-2-butenal enhanced TRAIL-induced apoptosis in ovarian cancer cells via down regulation of STAT3 pathway, 18 bee venom toxin and melittin suppressed ovarian cancer cell growth through induction of death receptors and inhibition of STAT3 pathway. 19 Moreover, it was demonstrated that blocking STAT3 activation with shRNA or siRNA could suppress ovarian cancer cell growth.…”
Section: Discussionsupporting
confidence: 68%
“…A novel oncolytic adenovirus, a STAT3 inhibitor HO‐3867 and a synthetic triterpenoid CCDO‐Me showed inhibitory effect on cancer cell growth via blocking STAT3 signaling pathway in ovarian cancer . In our previous study, we also found that (E)‐2,4‐bis(p‐hydroxyphenyl)‐2‐butenal, snake venom toxin, bee venom suppressed ovarian cancer cell growth via inhibition of STAT3 …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…We previously identified BHPB, a tyrosine-fructose MR product as a STAT3 inhibitor, which has potential therapeutic properties against multiple diseases including RA15161718192021222333. Despite its multiple pharmacological properties, the major drawback of BHPB in drug development is its lack of drug-likeness properties and limited chemical stability.…”
Section: Discussionmentioning
confidence: 99%
“…This action mediates the potent therapeutic effects of BHPB against RA14 as well as Alzheimer’s disease151617, and tumour growth181920212223. However, its drug-likeness is not relevant for drug development because it has a low chemical stability, low solubility, and high toxicity.…”
mentioning
confidence: 99%